Situation of young radiation oncologists, medical physicists and radiation biologists in German-speaking countries: results from a web-based survey of the Young DEGRO working group - Krug, David (Strahlentherapie und Onkologie, 2016)
Background and purposeThe working group “Young DEGRO” (yDEGRO) was established in 2014 by the German Society of Radiation Oncology (DEGRO). We aimed to assess the current situation of young radiation oncologists, medical physicists and radiation biologists.MethodsAn online survey that included 52 questions or statements was designed to evaluate topics related to training, clinical duties and research opportunities. Using the electronic mailing list of the DEGRO and contact persons at university hospitals in Germany as well as at four hospitals in Switzerland and Austria, young professionals employed in the field of radiation oncology were invited to participate in the survey.ResultsA total of 260 responses were eligible for analysis. Of the respondents 69 % had a professional background in medicine, 23 % in medical physics and 9 % in radiation biology. Median age was 33 years. There was a strong interest in research among the participants; however a clear separation between research, teaching and routine clinical duties was rarely present for radiation oncologists and medical physicists. Likewise, allocated time for research and teaching during regular working hours was often not available. For radiation biologists, a lack of training in clinical and translational research was stated.ConclusionThis survey details the current state of education and research opportunities in young radiation oncologists, medical physicists and radiation biologists. These results will form the basis for the future working program of the yDEGRO.
Gesehen am 28.11.2018